The Virtual Care Experience of Patients Diagnosed With COVID-19. (16th April 2021) - Raffan, Freya; Anderson, Teresa; Sinclair, Tim; Shaw, Miranda; Amanatidis, Sue; Thapa, Rajip; Nilsson, Sarah Jane; Jagers, Dianna; Wilson, Andrew; Haigh, Fiona
Virtual models of care are seen as a sustainable solution to the growing demand for health care. This paper analyses the experience of virtual care among patients diagnosed with COVID-19 in home isolation or health hotel quarantine using a patient-reported experience questionnaire. Results found that patients respond well to virtual models of care during a pandemic. Lessons learned can inform future developments of virtual care models.